New skills for new jobs: Work agency as a necessary condition for successful lifelong learning - Harteis, Christian; Goller, Michael (Promoting, assessing, recognizing and certifying lifelong learning)

RSA-Full Domain Hash Revisited - Rath, Timo
RSA Full Domain Hash ist im Zufallsorakelmodell ein EUF-CMA sicheres Signaturverfahren (existentially unforgeable under chosen-message attacks). Der Sicherheitsbeweis wird unter anderem in der Vorlesung Einführung in die Kryptographie vorgestellt. Auch bei einer genaueren Analyse verliert man bei der Reduktion einen Faktor \nicefrac{1}{q_{s}}(wobei q_{s}die Anzahl der Anfragen an das Signaturorakel darstellt), was für die Praxis in relativ großen Systemparametern (RSA-Modul) resultiert [1].Seit der Veröffentlichung von [2] wurde geglaubt, dass der Faktor \nicefrac{1}{q_{s}}optimal ist. Erst zehn Jahre später offenbarten die Autoren von [3] einen Fehler in [2] und zeigten eine bessere Reduktion allerdings unter einer etwas stärkeren Sicherheitsannahme.Die Ergebnisse aus [3] lassen sich auf PSS-Verfahren (Probabilistic Signature Scheme), das z.B. in PKCS #1 benutzt wird, übertragen und sind somit von großer Bedeutung für die Praxis. Weiterhin sind die in den Beweisen verwendete Techniken nützlich auch bei anderen kryptographischen Verfahren.In Rahmen dieser Arbeit sollen die entsprechenden Sicherheitsbeweise aufgearbeitet und dessen Auswirkungen für die Praxis analysiert werden.[1] J.S. Coron, “On the Exact Security of Full Domain Hash”, CRYPTO 2000. LNCS 1880, pp. 229-235, 2000.[2] J.S. Coron, “Optimal security proofs for PPS and other signature schemes”, EUROCRYPT 2002. LNCS 2332, pp 272-287, 2002.[3] S.A. Kakvi and E. Kiltz, “Optimal Security Proofs for Full Domain Hash, Revisited”, in EUROCRYPT 2012. LNCS 7237, pp 537-553, 2012.

The challenge of assessing the market value of private companies using a standardised combination method for tax purposes--Lessons to be learnt from past experience - Müller, Jens (European Accounting Review)
When taxes on capital or wealth are levied, in most countries companies have to be assessed in terms of their market value (MV). Estimating the MV of private companies for tax purposes is a challenging task for tax authorities as MVs are not available. In this study, I empirically analyse to what extent an accounting-based tax valuation method for private companies, a simplified residual income model, succeeds in matching the MV. I refer to the mandatory Standardised Combination Model that is a special case of methods commonly used in several countries. In the absence of market prices for private companies, I use a sample of small German public companies as a proxy. I validate this approach using a sensitivity analysis that involves matching the sample of public companies with that of private companies. The results imply that the mandatory Standardised Combination Model leads to a severe unequal treatment not only between public and private companies but also among private companies across and within industries. Furthermore, I simulate the effects of variation in the key parameters and highlight their impact on the approximation quality of the Standardised Combination Method. The findings are relevant to tax reform discussions as well as to tax policy-makers and practitioners in many countries.
Keywords: Challenge of Assessing; Tax Purposes

Routing Games with Progressive Filling - Harks, Tobias; Höfer, Martin; Schewior, Kevin; Skopalik, Alexander (Proceedings of the 33rd Annual IEEE International Conference on Computer Communications (INFOCOM'14))
Max-min fairness (MMF) is a widely known approach to a fair allocation of bandwidth to each of the users in a network. This allocation can be computed by uniformly raising the bandwidths of all users without violating capacity constraints. We consider an extension of these allocations by raising the bandwidth with arbitrary and not necessarily uniform time-depending velocities (allocation rates). These allocations are used in a game-theoretic context for routing choices, which we formalize in progressive filling games (PFGs).We present a variety of results for equilibria in PFGs. We show that these games possess pure Nash and strong equilibria. While computation in general is NP-hard, there are polynomial-time algorithms for prominent classes of Max-Min-Fair Games (MMFG), including the case when all users have the same source-destination pair. We characterize prices of anarchy and stability for pure Nash and strong equilibria in PFGs and MMFGs when players have different or the same source-destination pairs. In addition, we show that when a designer can adjust allocation rates, it is possible to design games with optimal strong equilibria. Some initial results on polynomial-time algorithms in this direction are also derived.

RoBuSt: A Crash-Failure-Resistant Distributed Storage System - Scheideler, Christian; Setzer, Alexander; Eikel, Martina (Proceedings of the 18th International Conference on Principles of Distributed Systems (OPODIS))
In this work we present the first distributed storage system that is provably robust against crash failures issued by an adaptive adversary, i.e., for each batch of requests the adversary can decide based on the entire system state which servers will be unavailable for that batch of requests. Despite up to \gamma n^{1/\log\log n} crashed servers, with \gamma>0 constant and n denoting the number of servers, our system can correctly process any batch of lookup and write requests (with at most a polylogarithmic number of requests issued at each non-crashed server) in at most a polylogarithmic number of communication rounds, with at most polylogarithmic time and work at each server and only a logarithmic storage overhead. Our system is based on previous work by Eikel and Scheideler (SPAA 2013), who presented IRIS, a distributed information system that is provably robust against the same kind of crash failures. However, IRIS is only able to serve lookup requests. Handling both lookup and write requests has turned out to require major changes in the design of IRIS.

Auswirkungen des Bologna-Prozesses: Eine Expertise der Hochschuldidaktik - Harteis, Christian (Herausforderung kompetenzorientierte Hochschule)

Investigating intuition under the perpective of expertise: Experiences from two experimental studies - Harteis, Christian (Handbook of intuition research methodology)

Response Time-Optimized Distributed Cloud Resource Allocation - Keller, Matthias; Karl, Holger (Proceedings of the SIGCOMM workshop on Distributed cloud computing)
In the near future many more compute resources will be available at different geographical locations. To minimize the response time of requests, application servers closer to the user can hence be used to shorten network round trip times. However, this advantage is neutralized if the used data centre is highly loaded as the processing time of re- quests is important as well. We model the request response time as the network round trip time plus the processing time at a data centre.We present a capacitated facility location problem formal- ization where the processing time is modelled as the sojourn time of a queueing model. We discuss the Pareto trade-off between the number of used data centres and the resulting response time. For example, using fewer data centres could cut expenses but results in high utilization, high response time, and smaller revenues.Previous work presented a non-linear cost function. We prove its convexity and exploit this property in two ways: First, we transform the convex model into a linear model while controlling the maximum approximation error. Sec- ond, we used a convex solver instead of a slower non-linear solver. Numerical results on network topologies exemplify our work.

Reputationssysteme für zusammengesetzte Dienstleistungen - Pahl, David

Relocatable Hardware Threads in Run-Time Reconfigurable Systems - Wold, Alexander; Agne, Andreas; Torresen, Jim (Proceedings of the 10th International Symposium on Reconfigurable Computing: Architectures, Tools, and Applications)
Run-time reconfiguration provides an opportunity to increase performance, reduce cost and improve energy efficiency in FPGA-based systems. However, run-time reconfigurable systems are more complex to implement than static only systems. This increases time to market, and introduces run-time overhead into the system. Our research aims to raise the abstraction level to develop run-time reconfigurable systems. We present operating system extensions which enable seamless integration of run-time reconfigurable hardware threads into applications. To improve resource utilization, the hardware threads are placed on a fine granularity tile grid. We take advantage of a relocatable module placer targeting modern FPGA to manage the reconfigurable area. The module placer accurately models the FPGA resources to compute feasible placement locations for the hardware threads at run-time. Finally, we evaluate our work by means of a case study that consists of a synthetic application to validate the functionality and performance of the implementation. The results show a reduction in reconfiguration time of up to 42% and more than double resource utilization.